Unveiling the Influence of Social Media Marketing on Purchase Decision with Brand Awareness and E-WOM as Mediators Among Wizzmie Yogyakarta Consumers - Reza Yudha Pradana; Budi Setiawan; Putri Dwi Cahyani (Amkop Management Accounting Review (AMAR), 2026)
The development of social media has shaped people's consumption patterns, including in the digital purchase of culinary products. Wizzmie, as a contemporary noodle restaurant, utilizes social media as a promotional strategy to attract consumers in Yogyakarta. This study aims to analyze the influence of Social Media Marketing on Purchase Decision with Brand Awareness and Electronic Word of Mouth (e-WOM) as mediating variables. This study uses a quantitative method through a questionnaire distributed to 211 Wizzmie consumers who actively use social media. The analysis technique uses Partial Least Square - Structural Equation Modeling (PLS-SEM) with the SmartPLS version 4 application. The results show that Social Media Marketing has a positive and significant effect on Brand Awareness and e-WOM, but does not directly influence Purchase Decision. The variables of Brand Awareness and e-WOM were found to have a positive effect on Purchase Decision and were able to mediate the relationship between Social Media Marketing and Purchase Decision. These results confirm that Wizzmie Purchase Decision are not always influenced by promotions, but are more influenced by consumer brand awareness and peer recommendations.